HARMONIOUS AND OSMAN NASIR Or "LOVE OF LIFE AND POETRY" - Marhabo Qo’chqorova Khudoyberganovna (Galaxy International Interdisciplinary Research Journal, 2022)
This article analyzed the article "love of life and poetry" written about the work of the people’s poet of Uzbekistan Misyun Osman Nasir.